Harnessing the Power of Nature: Ananas comosus Extract Gel as an Alternative Topical Treatment for Grade 2 Burn Wounds - Kharmi Juni Yanti; Diah Adriani Malik; Novi Kusumaningrum (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Burn injuries remain a significant global health challenge, often leading to complications such as infection and delayed healing. Conventional treatments can be costly and may have side effects, prompting exploration into natural therapeutic alternatives. Ananas comosus (pineapple), rich in the enzyme bromelain, has demonstrated anti-inflammatory and wound-healing properties, suggesting its potential as a topical agent for burn wounds. This study aimed to evaluate the efficacy of a topical gel formulated from Ananas comosus extract in promoting the healing of grade 2 burn wounds in a Wistar rat model by assessing its impact on wound diameter and the levels of pro-inflammatory cytokines Interleukin-1 beta (IL-1β) and Interleukin-6 (IL-6). Methods: A true experimental study with a post-test only control group design was conducted using 30 male Wistar rats. Grade 2 burn wounds were induced on the dorsum of the rats. The rats were randomly assigned to six groups (n=5 per group): a normal control (KN, no treatment), negative control (K-), a positive control (K+, silver plus alginate hydrogel), and three treatment groups receiving topical Ananas comosus extract gel at concentrations of 15% (P1), 20% (P2), and 25% (P3) twice daily for 14 days. Wound diameter was measured on days 1, 3, 6, 9, 12, and 14 using the ImageJ application. On day 15, tissue samples were collected for IL-1β and IL-6 quantification via ELISA. Data were analyzed using Kruskal-Wallis and Mann-Whitney U tests for wound diameter, and One-Way ANOVA with LSD post-hoc test for cytokine levels, with p<0.05 considered significant. Results: Significant differences in burn wound diameter and levels of IL-1β and IL-6 were observed among the groups (p<0.05). The P2 group (20% pineapple extract gel) exhibited the most significant reduction in wound diameter compared to the negative control and was comparable to the positive control group. This group also showed a marked decrease in IL-1β and IL-6 levels, with IL-1β levels similar to the positive control and IL-6 levels significantly lower than the untreated group and approaching those of the positive control. Conclusion: Topical application of 20% Ananas comosus extract gel effectively accelerated the healing of grade 2 burn wounds and reduced the levels of pro-inflammatory cytokines IL-1β and IL-6 in Wistar rats. These findings support the potential use of pineapple extract as an alternative herbal topical therapy for burn injuries. Further research is warranted to explore optimal formulations and clinical applications in humans.